Fresno County Bar Association Bernie Witkin Luncheon at Fresno County Plaza Ballroom - Watkins, Howard::::::::: (1988)
Fresno County Bar Association President Herbert Levy welcoming everyone to the luncheon; Bernie Witkin seated and smiling Fresno County Bar Association Banner on the wall "Established 1882"